A importância do lúdico na educação infantil: estudo de caso na Escola Municipal de Ensino Infantil e Fundamental Santa Ana - VIEIRA, Vívian Cristina de Souza (2023)
Ludicity has always been present in the history of humanity, being part of the culture of a country, a people. The play / play / toy is an intellectual activity and constant in childhood, being an inexhaustible source of learning and development. Through play, the child develops and develops skills and competences to deal with the environment. Learn about yourself and your culture. Based on this vision, the present research has as problematic: the importance of the playful one in the education of children, being the general objective of the research, to analyze the formation, the knowledge and the experiences of the teachers with the pedagogical practice in the infantile education, of as gives the teaching-learning process, as well as the importance of the application of games and games in this stage of motor development. The research searches through these almost infinite possibilities, which are the games, to analyze more deeply the process of knowledge of the ludic in early childhood education. The research was carried out at the Municipal School of Primary and Secondary Education Santa Ana, located in Vila Novo Planalto, in the Settlement Project (PA) Tuerê-I, municipality of Novo Repartimento-Pará. constants that help in the production of texts, permeating research of the ethnographic and descriptive type, in a qualitative and quantitative approach. The deepening of the theme was possible only from the theories of Blacksmith, Holland, Kishimoto, Arnais, among others. The teachers of the municipal school system were used as the population of the subjects surveyed. We chose a simple intentional sample, made up of two teachers of Early Childhood Education. As a research instrument, a questionnaire was chosen in which, answering the guiding questions raised in the research, it was verified that the teachers understand the importance of playfulness for the development of the students and their pedagogical doing.